Inhouse Quality Check System Improvement with Kanban System and Analysis Quality Control Circle - Santo Wijaya; Galih Supriadi; Fransisca Debora; P Yudi Dwi Arliyanto (Universitas Mercu Buana, 2021)
The development of digitalization has a positive impact to opportunity expand an innovation as a form of continuous improvement. One of the manufacturing companies, PT TCH, wants to implement Industry 4.0 innovation with the thought of integrating data and analytics supply chains. One of its applications is labeling error with a proportion value of 66% with an average error of 328 by creating a warning system for the Kanban system through the application of Quality Control Circle (QCC). The improvements made applying concepts Plan, Do, Check, and Action (PDCA) analysis by making improvements to the labeling system created from the PO database in marketing and creating a visualization of parts to help leverage product suitability. The results showed improvement with the decrease in cycle time from 265 seconds to 215 seconds and saving the cost IDR 70.48391 million / year. This research contributes theoretically in demonstrating the success of the application of QCC and in practical terms, it can provide a continuous increase in productivity and an actual decrease in process activities in the company.